HUBUNGAN E-BANKING DALAM MENINGKATKAN CITRA PRODUK TABUNGAN iB PLUS DAN KARTU BNI SYARIAH - Prapti Daliyanik (Faculty of Economic and Business, 2013)
The aim of this research is to analyze the correlation between e-banking to the images increasing of iB plus saving product and BNI Syariah card. And also to the customer’s perception of e-banking services on iB plus saving product and BNI Syariah card. The analysis method that used in this research is correlation analysis. The correlation between e-banking service on image product increasing is about 0,583 or 58,3%. It means that between e-banking services (based on customer’s perception) and image product increasing of iB plus product and BNI Syariah card has an average correlation.DOI: 10.15408/etk.v12i2.1911